A Review Study of Sweeping and Normal Impingement Jets - Hassan, Ahlam A.; Ismael, Muneer A. (Basrah Journal for Engineering Sciences, 2023)
This review focuses on the experimental and numerical studies of sweeping impingement jets that serve in cooling of hot surfaces. It is known that the impinging jets produce high-localized heat transfer coefficient. The sweeping jet covers a wider area on a hot target to improve the heat transfer rate, they could be used to increase the cooling rate of the impingement surface by disturbing the boundary layer. To display a readable survey, the current review was partitioned to four groups based on engineering configurations. The review shows that the sweeping nozzle gives better efficiency in heat transfer, improved Nusselt number and uniform target surface temperature, compared with the conventional normal jets. The current review reveals that the sweeping-jet mechanism can be achieved either by fluidic oscillator or by exciting a flexible wall forming an oscillating jet. Most of the fluidic oscillator researches are conducted experimentally (27%), while the researches that use flexible wall are about 24%.